2014
DOI: 10.1371/journal.pone.0086537
|View full text |Cite
|
Sign up to set email alerts
|

Licochalcone A Suppresses Migration and Invasion of Human Hepatocellular Carcinoma Cells through Downregulation of MKK4/JNK via NF-κB Mediated Urokinase Plasminogen Activator Expression

Abstract: Hepatocellular cell carcinoma (HCC) is one of the most commonly diagnosed cancers worldwide and in Taiwan. Chemoprevention of cancer with dietary bioactive compounds could potentially reverse, suppress, or prevent cancer progression. Licochalcone A (LicA) is a characteristic chalcone of licorice, which is the root of Glycyrrhiza inflate. It had been reported that LicA has anti-inflammatory, anti-microbial, and anti-tumor properties. However, the effects of LicA on the migration and invasion of human HCC cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
61
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 68 publications
(63 citation statements)
references
References 60 publications
(67 reference statements)
2
61
0
Order By: Relevance
“…Recent studies have reported that LCA and LCE, retrochalcones derived from root of Glycyrrhiza inflata, reduces inflammation, migration, angiogenesis, tumorigenesis, is antidiabetic, inducing cell cycle arrest and apoptosis in various cancer cell lines both in vitro and in vivo (10,16,27). LCA has been reported to induce bladder cancer apoptosis via modulation of mitochondria dysfunction and endoplasmic reticulum stress (12).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have reported that LCA and LCE, retrochalcones derived from root of Glycyrrhiza inflata, reduces inflammation, migration, angiogenesis, tumorigenesis, is antidiabetic, inducing cell cycle arrest and apoptosis in various cancer cell lines both in vitro and in vivo (10,16,27). LCA has been reported to induce bladder cancer apoptosis via modulation of mitochondria dysfunction and endoplasmic reticulum stress (12).…”
Section: Discussionmentioning
confidence: 99%
“…Licorice, the root and rhizome of several Glycyrrhiza species (Leguminosae), is an important natural sweetening agent and Licochalcone A, a natural chalconoid isolated from Glycyrrhiza inflata root, induces apoptosis via Sp1 and Sp1 regulatory proteins in oral squamous cell carcinoma is widely used as a herbal medicine (3). Licochalcone A (LCA) is a novel flavonoid isolated from licorice root and is known to possess several bioactivities such as antioxidant, antibacterial, antiparasitic, anti-angiogenesis and antitumor effects (10)(11)(12). It reduces significantly TNF-α-induced NF-κB activation, consequently resulting in decreased inflammatory cytokines production (13,14).…”
Section: Introductionmentioning
confidence: 99%
“…Decreased expression of phosphorylated p65 (a component of NF-κB) and N-cadherin (mesenchymal marker) and increased E-cadherin (epithelial marker) were also observed in LicAtreated SCC-25 cells [108]. LicA also attenuated the migratory and invasion ability of SK-Hep-1 and HA22T/VGH hepatic cancer cells [109]. This effect corresponded with an inhibition of the activity and expression of the serine protease, urokinase plasminogen activator (uPA), and decreased phosphorylation of JNKs and MKK4 in SK-Hep-1 cells [109].…”
Section: Antioxidant Effectsmentioning
confidence: 93%
“…LicA also attenuated the migratory and invasion ability of SK-Hep-1 and HA22T/VGH hepatic cancer cells [109]. This effect corresponded with an inhibition of the activity and expression of the serine protease, urokinase plasminogen activator (uPA), and decreased phosphorylation of JNKs and MKK4 in SK-Hep-1 cells [109]. Additionally, LicA suppressed the expression of NF-κB and its binding to the uPA promoter [109].…”
Section: Antioxidant Effectsmentioning
confidence: 93%
See 1 more Smart Citation